ENGLISH TEACHER TALK AT SENIOR HIGH SCHOOL NO 1 PAYAKUMBUH - Murekson Murekson (English Language Teaching and Research, 2017)
This paper contains partial result of a research. The purpose of the research was to describe the teacher talk of English teacher of SMAN 1 Payakumbuh. Teacher talk plays an important role in teaching learning English. Through teacher talk the classroom interaction is made. Unfortunately not all teachers pay attention closely to their talk. Too much teacher talking time automatically decrease the students talking time, therefore, limiting students’ opportunity to participate in class. However, The interactional feature of the talk is also crucial. These interactional features define the classroom mode of the teaching. The purposes of this research were to find (1) the interactional features of the teacher talk and (2) the classroom modes of the English teaching classroom. This research was qualitative research. It was conducted at SMAN 1 Payakumbuh. The population of this research was the English teachers and four of them became the sample of this study. The data were collected by recording the teaching and learning process. Each sample was recorded twice. The recording was then transcribed and analyzed by using SETT framework. The finding of the research shows that; (1) some constructive interactional features emerged. However there was still some room for improvement and; (2) The classroom mode of learning in order of generated the most were skill and system mode, managerial mode, material mode and classroom context mode. Keywords: Teacher talk, interactional features of teacher talk, effective features of teacher talk, SETT